2019
DOI: 10.1007/s10750-019-3885-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of macroinvertebrates in a South African stream treated with rotenone

Abstract: South Africa's Cape Fold Ecoregion supports a unique freshwater fish assemblage with many endemics. To mitigate impacts of alien invasive fishes on this unique assemblage, nature conservation authority CapeNature used rotenone to remove smallmouth bass (Micropterus dolomieu) from the Rondegat River. We investigated whether the rotenone treatments had an adverse impact on the aquatic macroinvertebrate community over the long-term, the first study of its kind in Africa. We monitored macroinvertebrates within tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Unfortunately, the possibility of this being a consequence of seasonal influences could not be investigated because the treated reservoir dried up in January 2018 owing to severe drought conditions, so collection of the 12‐month post‐treatment sample was not possible. The rapid recovery of macroinvertebrate communities in the present study is similar to findings by Bellingan et al (2019), who demonstrated the rapid recovery of macroinvertebrates in a South African stream treated with rotenone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unfortunately, the possibility of this being a consequence of seasonal influences could not be investigated because the treated reservoir dried up in January 2018 owing to severe drought conditions, so collection of the 12‐month post‐treatment sample was not possible. The rapid recovery of macroinvertebrate communities in the present study is similar to findings by Bellingan et al (2019), who demonstrated the rapid recovery of macroinvertebrates in a South African stream treated with rotenone.…”
Section: Discussionsupporting
confidence: 92%
“…documented (Bellingan et al, 2019;Vinson et al, 2010). Here we demonstrated that the treatment of a small reservoir using rotenone resulted in the eradication of common carp and a decrease in turbidity, a shift in plankton and invertebrate communities and changes in water quality.…”
Section: Conservation and Managementmentioning
confidence: 63%
See 1 more Smart Citation
“…Micropterus dolomieu were successfully extirpated from this river following two rotenone treatments 1 year apart and upgrading of an instream weir to prevent reinvasion from downstream sources (Weyl et al 2014). Extensive post-treatment monitoring of non-target aquatic invertebrates illustrated that despite short-term negative effects, the invertebrate community recovered relatively quickly to pre-intervention levels (Woodford et al 2013;Bellingan et al 2015Bellingan et al , 2019. Native fish from upstream of the treatment zone successfully recolonised the treatment zone, resulting in an increased area of occupancy for these species in the absence of M. dolomieu (Weyl et al 2014;Marr et al 2019).…”
Section: Micropterus Species (Black Basses)mentioning
confidence: 99%
“…At present, conservation efforts are focused on eradicating invaders, but those that are well established and strongly interspersed with natives cannot realistically be eradicated without affecting native species (i.e. with the use of rotenone; Bellingan et al, 2019). Accordingly, IAS removal may lead to unwanted and unexpected outcomes (Zavaleta, Hobbs & Mooney, 2001; Wallach, Ripple & Carroll, 2015).…”
Section: Introductionmentioning
confidence: 99%